Dinamika Kepemimpinan Direktur CV. Dwi Jaya di Desa Sanggalangit Kecamatan Gerokgak Kabupaten Buleleng - MUTTAQIEN, IRVAN; SUDARTA, WAYAN; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p04, 2018)
Leadership Dynamics of CV. Dwi Jaya’s Director in Sanggalangit Village, Sub- District of Gerokgak, Buleleng Regency The success of a company is influenced by the success of its employees. Employee success is influenced by the leadership dynamics of the director. CV Dwi Jaya agribusiness company is one of the companies engaged in the sale of fish seeds in the Sanggalangit Village of Gerokgak Sub-District, Buleleng Regency. The purpose of this research is to determine the level of leadership dynamics of the director and to investigate the levels of the three elements of leadership dynamics of directors in the company of cultivation and sale of fish seeds in CV Dwi Jaya. Descriptive analysis method was used to answer the purpose of the research. Effective human relations, decision-making process and control in leadership are the three variables in leadership dynamics that become the reference in this research.The result of descriptive analysis of leadership dynamics of director of CV Dwi Jaya is classified into a very good category with achievement score of 4.41. This can be seen from the three variables of leadership dynamics. Effective human relationship is categorized as very good with 4.45 achievement score, decision making process is very good with the score of 4.34 and leadership control is quite good with 4.41 score.